Mali : Fifth Review Under the Three-Year Arrangement Under the Extended Credit Facility and Request for Extension of the Arrangement and Rephasing of Disbursement-Staff Report; Joint IDA/IMF Debt Sustainability Analysis; Informational Annex; Staff Statement; Statement by the Executive Director for Mali; and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2011)
As a result of the Enhanced Highly Indebted Poor Countries (HIPC) Initiative and the Multilateral Debt Relief Initiative (MDRI), Mali's stock of external debt has declined significantly. The central feature of Mali's medium- and long-term macroeconomic outlook is the steady decline of annual gold production expected to be picked up only in part by other exports. Under baseline assumptions, all external debt and debt-service ratios remain below the policy-dependent thresholds throughout the projection period. Fiscal policy continues to be cautious.